A new approach towards the so-called recalcitrant seeds - Barbedo,Claudio José (2018)
ABSTRACT: Water is essential, irreplaceable, and indispensable for any kind of carbon-based-life metabolic activity. Water-dependent living beings are the expected pattern in nature. However, some organisms can survive for some time at a minimum water content, such as seeds of some species (orthodox seeds). Nevertheless, the expected standard life behavior is found in seeds of another group of species, the so-called recalcitrant seeds, which are sensitive to desiccation. A huge range of different behaviors can be found between these two groups, leading authors to consider that orthodoxy and recalcitrance is not an all-or-nothing situation. Notwithstanding, we are still too far from understanding the differences and similarities between all these kinds of seeds and this has been a serious barrier to the development of plant conservation technologies. A new approach to understanding the differences between these seeds is presented here based on seed maturation, environmental influences, and evolution. From this point of view, all kinds of seed behavior are contemplated and, consequently, some new perspectives are considered for the recalcitrant seed conservation technology, the most intensely desired technology nowadays in this area.